PENGEMBANGAN LEMBAR KERJA SISWA (LKS) PADA MATERI SISTEM PENCERNAAN KELAS VIII SMP DENGAN PENDEKATAN SAINTIFIK - Widya Astariana; Wan Syafi’i; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research was to develop the Student Worksheet development in digestion system content for grade VIII junior high school with scientific approach. The research was done at Faculty of Education, University of Riau in September until November 2015. The study refers to research approaches Research and Development using ADDIE models developed by Dick and Carry. Research carried out until the stage of development. The subjects is KD 3.6 junior high school grade VIII in digestion system content . Population and samples for limited trial randomly determine that the class VIII BK in SMP Negeri 1 Pekanbaru as many as 25 students. Result of the validation of the design, pedagogical and content aspects showed all student worksheets obtain an average score 3.64, 3.63, 3.62, 3.53, and 3.60 categorized as very valid while the student response from the aspect of design and content showed all student worksheet obtain an average score 3.58, 3.58, 3.57, 3.87, and 3.50 with the excellent category.Keywords: Development, Student Worksheet, Scientific Approach.2